ANALISIS KEUNTUNGAN USAHATANI POLA AGROFORESTRI PETANI LAHAN KERING (Studi Kasus: Desa Rejosari, Kec. Jatisrono,Kab. Wonogiri, Provinsi Jawa Tengah, 2011) - , Agung Septo Nur Pardiyanto, S.Hut. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis aims to analyze the relationship between the product patterns of agro forestry farming dry land farmers and farm production factors (labor and capital) and social factors (educational, institutional and interaction with the agricultural extension workers) with farm. Profits result gained from studies using the method multiple regressions showed that for the variable for maize, cassava, teak, and turmeric have significant values so that the higher value will cause a significant increase in the benefit of farmers as well. For the activeness of interaction with the field extension staff and members of the group activity in the value of significant value, so the social aspect of these two higher values will cause a significant increase in the benefit of farmers as well. As for goats, cattle feed and capital input has a value that is not significant so that its value will not affect the profits of farmers. For the labor variable has a significant negative value so that the higher value will reduce farm profit significantly.